2017
DOI: 10.3892/or.2017.6110
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR-19a inhibits colorectal cancer angiogenesis by suppressing KRAS expression

Abstract: The microRNA miR-19a is closely related to tumor formation and development and is a key oncogene. Previous studies have demonstrated that miR-19a is upregulated in multiple cancer types, including colorectal cancer (CRC). However, most of these experiments were performed in vitro, and consequently, the mechanisms underlying the effects of miR-19a on CRC are still unclear. Therefore, in the present study, we investigated the role of miR-19a in the development of solid CRC tumors. We generated KRAS 3'UTR-Mut by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
(33 reference statements)
2
19
0
1
Order By: Relevance
“…In other hand, it has been reported that the mutations of APC gene is very frequent in several CRC cell lines as Caco-2 (APC mutant), however, this mutation is not present in HCT116 cell line (APC WT) (Ilyas et al, 1997). Although mutations of KRAS, PIK3CA and APC correlate with VEGF expression and angiogenesis (Yeh et al, 2017;Chen et al, 2018;Lai et al, 2015;…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In other hand, it has been reported that the mutations of APC gene is very frequent in several CRC cell lines as Caco-2 (APC mutant), however, this mutation is not present in HCT116 cell line (APC WT) (Ilyas et al, 1997). Although mutations of KRAS, PIK3CA and APC correlate with VEGF expression and angiogenesis (Yeh et al, 2017;Chen et al, 2018;Lai et al, 2015;…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In contrast, miR-19a-3p expression is reduced in osteosarcoma, and silencing miR-19a-3p suppresses osteosarcoma cell proliferation and induces apoptosis [32]. In addition, miR-19a-3p is reported to be down-regulated and to further inhibit the angiogenesis of CRC cells [33]. However, how miR-19a-3p was controlled in CRC remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, miR-19a-3p expression is reduced in osteosarcoma, and silencing miR-19a-3p suppresses osteosarcoma cell proliferation and induces apoptosis [32]. In addition, miR-19a-3p was reported to be downregulated and further inhibited the angiogenesis of CRC cells [33]. However, how miR-19a-3p was controlled in CRC remained unclear.…”
Section: Discussionmentioning
confidence: 99%